The relation between computational thinking and logical thinking in the context of robotics education - Veenman, Kim; Tolboom, Jos L. J.; van Beekum, Olivier (Frontiers in Education, 2022)
Computational thinking is nowadays a student skill on a steep rise. Assessment of this skill is nevertheless still subject of debate. This pilot study focuses on examining whether computational thinking and logical thinking are related. Therefore, we investigated the effect of a robotics course with respect to logical thinking and computational thinking of 14-year-old Dutch students. Thirty-five students were pre-tested to assess their logical thinking and post-tested for their logical thinking and their computational thinking. The intervention group (N=11) followed a robotics course in between pre- and post-test. This study’s results show a significant positive correlation between computational thinking and logical thinking. The study, with a small sample size, does not show an effect of the robotics course on either logical thinking, nor on computational thinking.